International STEM graduate students: reaching a deeper understanding. Issue 3 (12th November 2018) - Yu, Jen-Chien; Trei, Kelli Jean; Carlstone, Jamie
Abstract : Purpose: The purpose of this paper is to better understand the perceptions international STEM students have of the library and higher education based on their responses to the Ithaka S+R Graduate Student Survey. Design/methodology/approach: To better understand these groups, this study conducted the Mann–Whitney–Wilcoxon test on the Ithaka survey results to compare the groups and identify any statistically significant differences that the international STEM graduate students group (ISG) has to other groups. Findings: This paper found that ISG valued Higher Education objective variables more than the non-ISG group, with the exception of one question. The ISG group also valued 7 of the 13 role of the library (ROL) variables statistically different. Research limitations/implications: Since the students self-reported as international or STEM, the authors are unable to assess whether the response pool is representative of the university as a whole. Practical implications: By understanding how international/STEM students may differ from other populations, libraries can better design spaces and services for these groups. Originality/value: Existing studies tend to focus on international students or STEM students and information literacy. This study intends to fill a gap in the understanding of how these groups perceive the ROL and their education.